FOOD SECURITY AND THE MARKET FOR CROP PRODUCTION IN THE CHERNIVTSI REGION - ZAIACHUK, Myroslav; TIMISH, Rodika (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. The prerequisites for the study are methodological developments of the scientists of the Institute of Agrarian Economics and attempts to implement them at the regional level. They are based on the assessment of the food market capacity, taking into account the regional agricultural specialisation of the production of certain agricultural products, the purchasing power of the population and the demand for various types of agricultural products. Simultaneously, this implies taking into account, in addition to intra-regional production and demand, inter-regional product movement and the formation of expert potential. The article considers the concept of the food market and the features of its formation. The minimum and rational consumption norms are indicated. The object of the study is the food market of the regional region from the position of filling it with plant products.Methods. The research methodology consists of assessing the actual volume of the capacity of the intra-regional consumer food market and agricultural product markets, taking into account the consumption of food products at the level of minimum and rational nutritional standards of the population of the regional region. To achieve the set goal, a number of scientific methods were used. Namely, horological; mathematical modelling; economic; balance and normative; abstraction and generalisation; statistical methods were used.Results. The current state of plant production development is analyzed and an assessment of the formation of supply on the food market with plant products in the Chernivtsi region is carried out. In the agriculture of the Chernivtsi region, the trends of dominance of plant production over livestock farming in the structure of agricultural production, growth in areas and gross yields of technical and fruit crops continue. Reduction in the number of cattle and the general dominance of agricultural formations in crop production (except for potato, vegetable, etc.) and households in livestock (except for poultry). When forming regional food markets, it is necessary to take into account such an aspect as the production of agricultural products by households for selfsufficiency rather than for sale.Conclusions. The regional food market for plant products in the Chernivtsi region can be considered quite balanced, characterized by potential niches for the production of vegetables, potatoes, grain products and export-oriented fruit growing. When forming regional food markets, it is necessary to take into account such an aspect as the production of agricultural products by households for the most part for self-sufficiency, and not for sale. There is also a certain share of products that are outside the scope of commodity-money relations. The possibilities of selling agricultural products by individual households have a significant number of infrastructure problems (place of sale, possibilities for storing products, packaging and sorting, etc.). All this provides non-competitive advantages to large agricultural enterprises for the formation of inflated prices.
Keywords: food market; food security; minimum consumption rate; rational consumption rate; agricultural production; crop production; rural population; urban population